Smarttransparency Or Smart Corruption? Pentagon Fraud Theory And Islamic Work Ethic On Corruption In Pertamina’s Gas Station Digitalization Project - Denari Dhahana Edtiyarsih (Journal of Creative Power and Ambition (JCPA), 2026)
This study adopts a qualitative research design employing a phenomenological approach to examine the case of corruption in the digitalization of fuel stations (SPBU) involving PT Pertamina and PT Telkom. The study utilizes content analysis of investigative journalism reports and relevant YouTube channels addressing the corruption case. The analytical coding framework is grounded in the Pentagon Fraud Theory and Islamic Work Ethic. The objective of this study is to analyze the determinants of corruption in the SPBU digitalization project based on the Pentagon Fraud Theory, which comprises pressure, opportunity, rationalization, competence, and arrogance. Additionally, the study explores the phenomenon from the perspective of Islamic Work Ethic. The findings indicate that pressure, opportunity, rationalization, and arrogance are the primary drivers of corruption in the SPBU digitalization project. Government ambition to accelerate digital transformation, direct appointment practices by PT Pertamina to PT Telkom, perceived entitlement to compensation due to workload, as well as a sense of seniority and perceived security stemming from employment within state-owned enterprises, collectively contributed to the perpetrators’ engagement in corrupt practices. Furthermore, the actors neglected key dimensions of Islamic Work Ethic, particularly fairness and generosity in the workplace, thereby reinforcing the propensity to engage in corrupt behavior.